A Study of Protein Energy Malnutrition with Respect to Breast Feeding Practices in Less Than Six Year Children - Ukarande, Balaji V; Nagaonkar, Ajit S (National Journal of Community Medicine, 2015)
Introduction: Breastfeeding is one of the most effective ways to en- sure child health and survival globally, less than 40% of infants under six months of age are exclusively breastfed. Method: Community based, cross sectional study in rural field prac- tice area in 476 under six children Results: The Proportion of undernutrition was more in, who has not exclusively breast fed (72.92% and 44.07%, p<0.001); who did not received colostrum (91.74% and 27.64%, p<0.0001); who received pre- lacteal feed (94.35% and 25.20%, p<0.05); Breast fed after 1hr of birth. (71.66% and 45.34%, p<0.0001); who has un-hygienic feeding practic- es (63.33% and 50.57% p<0.05); and who weaned after 6 months of age (67.11% 43.60%. p<0.001). Conclusion: Adequate breastfeeding counseling and support are es- sential for mothers and families to initiate and maintain optimal breastfeeding practices.